Effects of Video Modeling and Video Modeling Plus Prompting and Reinforcement on the Daily Living Skills of a Student with Autism - Wynkoop, Kaylee S.; Robertson, Rachel E.; Sobeck, Emily E. (Journal of the American Academy of Special Education Professionals, 2018)
Video modeling (VM) is an intervention that may be implemented to improve the daily living skills of students with autism. A multiple probe across behaviors design was employed to examine the effects of VM and VM plus prompting and reinforcement (VM+P&R) on the daily living skills of one elementary student with autism. The percentage of correctly completed steps according to a task analysis for each of three target daily living skills was measured across each condition. Results showed the student improved performance under the VM condition. However, further improvement was demonstrated under the VM+P&R condition. Implications for practitioners choosing between VM and VM+P&R and directions for future research are discussed.